Frailty modifies the effect of polypharmacy and multimorbidity on the risk of death among nursing home residents: Results from the SHELTER study - Zazzara, Maria Beatrice; Villani, Emanuele Rocco; Palmer, Katie; Fialova, Daniela; Corsonello, Andrea; Soraci, Luca; Fusco, Domenico; Cipriani, Maria Camilla; Denkinger, Michael; Onder, Graziano; Liperoti, Rosa (Frontiers in Medicine, 2023)
Background: Frailty, disability, and polypharmacy are prevalent in nursing home(NH) residents, often co-occurring with multimorbidity. There may be a complex interplay among them in terms of outcomes such as mortality. Aims of the study were to i)assess whether nursing home residents with polypharmacy(5-9 medications) or hyperpolypharmacy(≥10 drugs), have an increased risk of death and ii)whether any association is modified by the co-presence of frailty or disability. Methods: Cohort study with longitudinal mortality data including 4,023 residents from 50 European and 7 Israeli NH facilities(mean age=83.6 years, 73.2% female) in The Services and Health for Elderly in Long Term care(SHELTER) cohort study. Participants were evaluated with the interRAI-LongTerm Care assessment tool. Frailty was evaluated with the FRAIL-NH scale. Hazard ratio (HR) of death over 12 months was assessed with stratified Cox proportional hazards models adjusted for demographics, facilities, and cognitive status. Results: 1042(25.9%) participants were not on polypharmacy, 49.8%(n=2002) were on polypharmacy, and 24.3%(n=979) on hyperpolypharmacy. Frailty and disability mostly increased risk of death in the study population(frailty: HR= 1.54, 95%CI 1.23-1.94; disability: HR= 2.03, 95%CI 1.66-2.50). Among non-frail participants, multimorbidity(HR=1.35, 95%CI=1.05-1.74) and hyperpolypharmacy(HR=1.29, 95%CI=1.01-1.84) were associated with higher risk of death. Among frail participants, no other factors were associated with mortality. Polypharmacy and multimorbidity were not associated with mortality after stratification for disability. Conclusions: Frailty and disability are the strongest preditors of death in NH residents. Multimorbidity and polypharmacy increase mortality only in people without frailty. This may be relevant to identify a population that could benefit from tailored deprescription.